Policies to promote collaboration in science, technology and innovation for development : the role of science, technology and innovation parks (UN New YorkUS, 2015)
Presents some considerations on the dimensions of the performance of STI parks as instruments of innovation policy that may be of relevance for policymakers in developing countries and suggests several issues for discussion.
Note by the UNCTAD Secretariat.